Neutralization of both IL-1α/IL-1β plays a major role in suppressing combined cigarette smoke/virus-induced pulmonary inflammation in mice. (June 2017) - Bucher, Hannes; Mang, Samuel; Keck, Martina; Przibilla, Michèl; Lamb, David J.; Schiele, Felix; Wittenbrink, Mareike; Fuchs, Klaus; Jung, Birgit; Erb, Klaus J.; Peter, Daniel
Abstract: Smoking is an important risk factor for the development of chronic obstructive pulmonary disease (COPD) and viral infections are believed to be major triggers of exacerbations, which periodically lead to a worsening of symptoms. The pro-inflammatory IL-1 family members IL-1α and IL-1β are increased in COPD patients and might contribute to disease pathology. We investigated whether individual or combined inhibition of these cytokines reduced lung inflammation in cigarette smoke (CS)-exposed and H1N1-infected BALB/c mice. Animals were treated with individual or combined antibodies (Abs) directed against IL-1α, IL-1β or IL-1R1. Cells in BAL fluid and cytokines/chemokines in lung homogenate were determined. The viral load was investigated. Blocking IL-1α had significant suppressive effects on total cells, neutrophils, and macrophages. Furthermore, it reduced KC levels significantly. Blocking of IL-1β did not provide significant activity. In primary human bronchial epithelial air-liquid-interface cell cultures infected with H1N1, IL-1α Abs but not IL-1β Abs reduced levels of TNF-α and IL-6. Concomitant usage of Abs against IL-1α/IL-1β revealed strong effects in vivo and reduced total cells, neutrophils and macrophages. Additionally, levels of KC, IL-6, TNF-α, MCP-1, MIP-1α and MIP-1β were significantly reduced and ICAM-1 and MUC5 A/C mRNA expression was attenuated. The viral load decreased significantly upon combined IL-1α/IL-1β Ab treatment. Blocking the IL-1R1 provided significant effects on total cells, neutrophils and macrophages but was inferior compared to inhibiting both its soluble ligands IL-1α/IL-1β. Our results suggest that combined inhibition of IL-1α/IL-1β might be beneficial to reduce CS/H1N1-induced airway inflammation. Moreover, combined targeting of both IL-1α/IL-1β might be more efficient compared to individual neutralization IL-1α or IL-1β or inhibition of the IL-1R1.